2007
DOI: 10.1093/rheumatology/kem355
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in the surfactant proteins in systemic sclerosis in Japanese: T/T genotype at 1580 C/T (Thr131Ile) in the SP-B gene reduces the risk of interstitial lung disease

Abstract: In SSc, where massive fibrosis occurs, possession of the T/T genotype in the SP-B gene would reduce the risk of ILD in Japanese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…SP-BC/T1580 is functionally one of the most important (26,27). This SP-BC/T1580 polymorphism is not only associated with pneumonia and pneumonia-induced ARDS (21,28,29), but also with neonatal respiratory distress syndrome (RDS) (30), and interstitial lung disease (ILD) (31). The detailed mechanisms for the increased susceptibility of SP-B C allele to these pulmonary diseases are unknown (6,27,32).…”
Section: Resultsmentioning
confidence: 99%
“…SP-BC/T1580 is functionally one of the most important (26,27). This SP-BC/T1580 polymorphism is not only associated with pneumonia and pneumonia-induced ARDS (21,28,29), but also with neonatal respiratory distress syndrome (RDS) (30), and interstitial lung disease (ILD) (31). The detailed mechanisms for the increased susceptibility of SP-B C allele to these pulmonary diseases are unknown (6,27,32).…”
Section: Resultsmentioning
confidence: 99%
“…The SNP (rs11130866 C/T) studied in the present work has been found to be associated with several pulmonary diseases in several independent groups [13] [7,12]. For instance, individual with C/C genotype was found more susceptible to RDS [29] while individual with T/T genotype was found to protect the patients with SSC against the development of ILD[7].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, individual with C/C genotype was found more susceptible to RDS [29] while individual with T/T genotype was found to protect the patients with SSC against the development of ILD[7]. The individuals carrying one or more C allele had more severe lung injury and required MV compared to those with T/T genotype [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of another study have shown the incidence of SP-B deficiency in African Americans to be higher than in Caucasian Americans (12). The SP-B gene mutation has been shown to be associated with some respiratory diseases, including neonatal RDS, acute respiratory distress syndrome, congenital pulmonary alveolar proteinosis, adult chronic obstructive pulmonary emphysema and chronic lung diseases in children (1315). …”
Section: Discussionmentioning
confidence: 99%